Research ethics committees: their importance in building a vibrant research community in Kazakhstan - Howie, Peter (KAZGUU University, Nazarbayev University, 2018)
The functions and benefits of research ethics committees in developing and transition economies go much further than those in developed countries. Firstly, a fundamental objective of a research ethics committee in both developing and transition economics is to establish the public's trust in both research and investigators.
Keywords: Academic Integrity; Research Ethics; Education; Collaboration; Trust Building